Q. 23.7( 70 Votes )

# Solve the following simultaneous equations.

i. 2x + y = 5; 3x - y = 5

ii. x - 2y = -1; 2x - y = 7

iii. x + y = 11; 2x - 3y = 7

iv. 2x + y = -2; 3x - y = 7

v. 2x - y = 5; 3x + 2y = 11

vi. x - 2y = -2; x + 2y = 10

Answer :

(i)

2x + y = 5

⇒ y = 5 - 2x eq.[1]

3x - y = 5

Using eq.[1] we have

⇒ 3x - (5 - 2x) = 5

⇒ 3x - 5 + 2x = 5

⇒ 5x = 10

⇒ x = 2

Using 'x' in eq.[1]

⇒ y = 5 - 2(2)

⇒ y = 5 - 4 = 1 cm

(ii)

x - 2y = -1

⇒ x = 2y - 1 eq.[1]

2x - y = 7

Using eq.[1], we have

⇒ 2(2y - 1) - y = 7

⇒ 4y - 2 - y = 7

⇒ 3y = 9

⇒ y = 3

Using this value in eq.[1]

⇒ x = 2(3) - 1

⇒ x = 5

(iii)

x + y = 11

⇒ y = 11 - x eq.[1]

2x - 3y = 7

Using eq.[1], we have

⇒ 2x - 3(11 - x) = 7

⇒ 2x - 33 + 3x = 7

⇒ 5x = 40

⇒ x = 8

Using this in eq.[1]

⇒ y = 11 - 8

⇒ y = 3

(iv)

2x + y = -2

⇒ y = -2x - 2 eq.[1]

3x - y = 7

Using eq.[1]

3x - (-2x - 2) = 7

⇒ 3x + 2x + 2 =7

⇒ 5x = 5

⇒ x = 1

Using this in eq.[1]

⇒ y = -2(1) - 2

⇒ y = -2 - 2 = -4

(v)

2x - y = 5

⇒ y = 2x - 5 eq.[1]

3x + 2y = 11

Using eq.[1]

⇒ 3x + 2(2x - 5) = 11

⇒ 3x + 4x - 10 = 11

⇒ 7x = 21

⇒ x = 3

Using this in eq.[1]

⇒ y = 2(3) - 5

⇒ y = 1

(vi)

x - 2y = -2

x = 2y - 2 eq.[1]

x + 2y = 10

using eq.[1], we have

⇒ 2y - 2 + 2y = 10

⇒ 4y = 12

⇒ y = 3

Using this in eq.[1]

⇒ x = 2(3) - 2

⇒ x = 4

Rate this question :

Find the factors of the polynomials given below.

√3x^{2} + 4x + √3

Factorize the following polynomials.

(y+2) (y+3) (y-3) (y + 8) + 56

MHB - Math Part-IFactorize the following polynomials.

(x-5)^{2}–(5x-25)-24

Find the factors of the polynomials given below.

2x^{2} + x – 1

Factorize the following polynomials.

(x – 3) (x- 5) (x – 4)^{2} – 6

Find the factors of the polynomials given below.

1/2 x^{2} - 3x + 1